Continuous adductor canal block is a better choice compared to single shot after primary total knee arthroplasty: A meta-analysis of randomized controlled trials. (December 2019) - Wang, Chen; Chen, Zhengjie; Ma, Xinlong
Abstract: Background: The advantages of continuous adductor canal block (CACB) over single shot ACB (SACB) are still debatable for pain management after total knee arthroplasty (TKA). The aim of this study was to investigate which ACB method provides better pain relief after TKA. Methods: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science were searched without any language restrictions. Only randomised clinical trials (RCTs) were included in this meta-analysis. The primary outcome was pain score, whereas the secondary outcomes included opioid consumption, post-operative complication, and length of stay. Results: Eight RCTs with a total of 642 patients were included. The overall evidence for outcomes was moderate. The pooled data indicated that the use of CACB after TKA surgery was associated with lower pain score at rest or movement ( P  < 0.00001), cumulative morphine consumption ( P  = 0.003), and length of hospital stay ( P  = 0.03) compared with SACB, with no difference in nausea or vomiting rate ( P  = 0.55). Conclusions: Compared with SACB, CACB provides better analgesia after TKA. Therefore, CACB is recommended as an analgesic method for early postoperative pain treatment after TKA. Highlights: CACB after TKA surgery was associated with lower pain score compared with SACB. We found that CACB and SACB provided similar rate of nausea or vomiting after TKA. It remains unclear whether CACB results in better functional outcomes after TKA.